An algebraic approach to sesqui-linear curves in Desarguesian planes - Swart, Henda C.(Hendrika Cornelia Scott) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1970.